The role of statins in prevention and treatment of community acquired pneumonia: a systematic review and meta-analysis. - Abdur Rahman Khan; Muhammad Riaz; Aref A Bin Abdulhak; Mohamad A Al-Tannir; Musa A Garbati; Patricia J Erwin; Larry M Baddour; Imad M Tleyjeh (PLoS ONE, 2013)
Background Emerging epidemiological evidence suggests that statins may reduce the risk of community-acquired pneumonia (CAP) and its complications. Purpose Performed a systematic review to address the role of statins in the prevention or treatment of CAP. Data source Ovid MEDLINE, Cochrane, EMBASE, ISI Web of Science, and Scopus from inception through December 2011 were searched for randomized clinical trials, cohort and case-control studies. Study selection Two authors independently reviewed studies that examined the role of statins in CAP. Data extraction Data about study characteristics, adjusted effect-estimates and quality characteristics was extracted. Data synthesis Eighteen studies corresponding to 21 effect-estimates (eight and 13 of which addressed the preventive and therapeutic roles of statins, respectively) were included. All studies were of good methodological quality. Random-effects meta-analyses of adjusted effect-estimates were used. Statins were associated with a lower risk of CAP, 0.84 (95% CI, 0.74-0.95), I(2) = 90.5% and a lower short-term mortality in patients with CAP, 0.68 (95% CI, 0.59-0.78), I(2) = 75.7%. Meta-regression did not identify sources of heterogeneity. A funnel plot suggested publication bias in the treatment group, which was adjusted by a novel regression method with a resultant effect-estimate of 0.85 (95% CI, 0.77-0.93). Sensitivity analyses using the rule-out approach showed that it is unlikely that the results were due to an unmeasured confounder. Conclusions Our meta-analysis reveals a beneficial role of statins for the risk of development and mortality associated with CAP. However, the results constitute very low quality evidence as per the GRADE framework due to observational study design, heterogeneity and publication bias.